KUALITAS LAYANAN PERPUSTAKAAN DAN INFORMASI PERPUSTAKAAN NASIONAL RI - Fathmi Fathmi (Perpustakaan Nasional RI, 2017)
This study was aimed at determining the quality of library and information services in the National Library of Indonesia based on perception and expectation of visitors at the three dimensions of LibQual+TM, namely affect of service, library as place and information control. Descriptive quantitative was used as the study method. Data collection techniques used were questionnaires with 129 visitor respondents and literature studies that were relevant to and support this study. The results showed that the quality of service and information in the National Library of Indonesia was good because the perception score of visitors was higher than the minimum expectation, yet it had not reached the ideal expectation. This means visitors were satisfied with the services provided by the National Library of Indonesia. Of the three quality dimensions of LibQual+TM, information control (IC) was the highest with an average value of AG 0.89, followed by affect of service with an average AG value of 0.79. The indicator of clean and well maintained library was the one with the greatest positive AG of 1.16. The strengths of services of the National Library of Indonesia lay in the condition of the library that was clean and well maintained at all times; the library service hour that matched the predetermined schedule; comfortable library rooms; and the convenience when getting the information. The weaknesses of library and information services of the National Library of Indonesia were on e-resources collections and printed collections that did not meet the information needed by visitors.